Knitted fabric simulation: A survey - Hu, Xinrong; Wang, Meng; Liu, Junping; Liang, Jinxing; Yang, Kai; Luo, Ruiqi; Fang, Fei; Peng, Tao (Computer animation and virtual worlds, 2024)
Knitted fabric simulation seeks to create lifelike virtual representations of various knitted items like sweaters and socks using mathematical models and advanced simulation techniques. Significant advancements have been achieved in this area. Visual simulations of these fabrics now boast enhanced details, textures, and colors, closely resembling real‐world counterparts. Additionally, physical simulations have improved the movement and deformation aspects of virtual knitted fabrics, enhancing their realism. However, challenges remain. One major concern is the computational demands of these simulations, which can hinder real‐time interactions. Another issue is refining the accuracy of material models, especially when simulating diverse fibers and textures. This paper aims to review the current state of knitted fabric simulation and speculate on its future directions. By analyzing the current situation of knitted fabric simulation, this paper introduces several commonly used traditional knitted fabric simulation methods, including microfabric simulation, mass‐spring model and finite element analysis, and also introduces the new Methods based on zero curvature geometry proposed in recent years. This paper also proposes that the combination of physical simulation and machine learning can accurately predict the behavior of textile fabrics and minimize the cost and production time. The prospect of this method is also proposed.